The Utility of RGB Color for Discrimination of Lunar Maturity and Composition - Blewett, David T.; Choi, Tiffanie X.; Zheng, YongChun; Cloutis, Edward A. (Earth and space science (Hoboken, N.J.), 2023)
We explore the extent to which red‐green‐blue (RGB) color images, such as those produced by a complementary metal oxide semiconductor (CMOS) Bayer‐filter camera, can be utilized for studying the maturity and composition of the lunar surface. RGB filters typically are quite broad, with considerable overlap among the three colors. Convolution of laboratory spectra for lunar samples to the RGB responsivities of the Chang'E‐3 rover's Panoramic Camera allowed determination of the correlations between color ratios (B/R, B/G, and G/R) and the sample maturity (Is/FeO) or composition (wt.% FeO or TiO2). In general, color ratios decrease as Is/FeO increases. When separate sample categories are considered, we find that the B/R ratio is a good predictor of Is/FeO for low‐Ti mare, low‐Fe highland, and moderate‐Fe highland soils. For high‐Ti mare soils, Is/FeO has little influence on the B/R ratio (due to the spectral effects of abundant ilmenite), and hence the ratio cannot be used to determine maturity. We also find that color ratios have no useful correlation with sample wt.% FeO or TiO2. Thus, in locations excluding the high‐Ti maria, RGB color data could be used to estimate soil maturity. We outline a concept for a multispectral imager based on a CMOS sensor with a Bayer‐like pattern of custom‐wavelength filters chosen specifically for lunar science applications. Plain Language Summary Typical color cameras capture light through pixels covered with red, green, and blue (RGB) filters, enabling images to mimic the visual response of the human eye. However, because the color filters are broad (transmit a wide range of wavelengths of light) and overlap to some extent, RGB images can be less useful for scientific purposes. We wanted to determine whether RGB images could be used to estimate certain characteristics of rocks and soils on the Moon. Using lab data for Apollo lunar samples, we determined that RGB images might be helpful for mapping a characteristic of the soil known as “maturity,” which is related to the length of time that the soil has been exposed on the lunar surface. This mapping technique could be applied to surfaces except for those soils containing high abundances of titanium. We also discuss a concept for a camera that could achieve greater science return than RGB by using a set of three filters that are customized for application to the Moon. Key Points Analyzed lunar sample spectra in terms of typical red‐green‐blue (RGB) camera bandpasses RGB color ratios can be used to estimate soil maturity of specific sample categories (low‐Fe highland, moderate‐Fe highland, low‐Ti mare) We present a concept for a camera based on a complementary metal oxide semiconductor sensor with custom pattern filters that are selected specifically for lunar composition and maturity mapping